Postacute Care Transitions: Developing a Skilled Nursing Facility Collaborative within an Academic Health System. Issue 3 (1st March 2019) - Conway, Sarah J; Parekh, Anand K; Hughes, Andrew H; Sylvester, Carol; Himmelrich, Sarah; Hebert, Lindsay C; Doyle, Damien; Bellantoni, Michele; Berkowitz, Scott A; ,
Abstract : Hospitals are under financial pressure to shorten hospitalizations and reduce readmissions. Current evidence suggests that postacute care‐associated rehospitalizations could be reduced by focusing on a concentrated referral network of preferred high‐quality skilled nursing facilities (SNFs). Hospitals, health systems, and health plans have taken several approaches to creating preferred provider networks to streamline and improve the quality of SNF discharges. We propose a collaborative framework for the establishment of a preferred postacute care network based on the experience of the Johns Hopkins Medicine Skilled Nursing Facility Collaborative and review early implementation challenges.